(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
A flat plate solar collector with cell polycarbonate absorber and transparent cover has been made and its experimental investigation carried out. The collector consists of a wooden box, into which, a layer of heat insulation with a mirror film and 4 mm thick cell polycarbonate sheet, as the absorber, are placed. The coherence between collector’s efficiency, heat carrier and ambient air temperature, as well as intensity of the solar radiation and heat power in the experimental investigation has been obtained. During the experimental examination the maximum temperature of the heat carrier reached 80˚C at the intensity of solar radiation about 0.8 kW/m2 and ambient air temperature around 32˚C. The efficiency of the collector reached 33-60%, depending on the intensity of solar radiation and surrounding air temperature.